INNOVATION ADOPTION IN THE AGRI-FOOD SYSTEM - Marcela Naves Costa Ribeiro; Eduardo Pinheiro Gondim de Vasconcellos (Encontro Internacional de Gestão, Desenvolvimento e Inovação (EIGEDIN), 2024)
The agri-food system is responsible for boosting the gross domestic product (GDP) of several countries, creating jobs, and feeding populations around the world. Several technologies have been developed by and for the agri-food system to remain competitive in an unstable and dynamic scenario. Innovation and its adoption process are complex constructs, approached from different perspectives. Therefore, the objective of this study was to identify, through a systematic review, the main innovations that are being adopted in the agri-food system, to clarify the paths and areas of research that organizations operating in the agri-food system should consider in order to remain competitive. The results showed that innovations are mainly related to the adoption of information and communication technologies (ICTs), the adoption of innovations in packaging, conservation methods, the use of nanotechnology and 3D printers. It was also found that the studies highlight the importance of networking and collaboration for innovation adoption processes to occur, and that innovations capable of promoting alternatives to sustainability challenges are currently considered the most attractive ans a great opportunity for the agri-food system. Thematic gaps were identified, as alternative proteins adoption by agri-food system organizations and innovation possibilities for agri-food SMEs, directing to future research about this topics.